Aktivitas Antibakteri dan Antimitotik dari Fungi yang Bersimbiosis dengan Spons - Maarisit, Wilmar; Minelko, Marstella; Jan, Tan Tjie (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Sponge-derived fungi are source of natural bioactive compounds. The aim of this research is to test the anti-bacterial and anti-mitotic activities from marine sponge-derived fungus. The sponge-derived fungus (strain TID.24041021-2) has been successfully isolated from sponge (strain TID.24041021-2) collected from the sea around Tidung Island. The morphology of this fungus has been identified and classified in the genus Wangiella sp. This fungus was cultivated in PDA with salinity 25 ppm for 21 days at room temperature, extracted with acetone, partitioned with ethyl acetate, and tested the anti-bacterial activity against Bacillus subtilis, Escherichia coli, and Staphylococcus aureus, and also tested the anti-mitotic activity using root tip cells of Allium cepat. The results showed that crude extract of ethyl acetate could inhibit the growth of B. subtilis 91.30-2.30 mm), E.coli (1.50-3.03 mm) dan S.aureus (2.80-5.0 mm) bacteria. Also, antimitotic activity from crude extract of ethyl acetate showed that there is chromosome abnormalities of 0.76 and 1.38 in extract concentration of 20% and 25%, respectively.Keywords : Sponge-derived fungi, anti-bacterial, anti-mitotic, chromosome abnormalities.